Accurate Exploration of the Intrinsic Lattice Thermal Conductivity of Si2N2O by Combined Theoretical and Experimental Investigations. Issue 3 (12th December 2015) - Wan, Peng; Tian, Zhilin; Luo, Yixiu; Liu, Bin; Wang, Jingyang
Abstract : Si2 N2 O is a promising ceramic with various structural and functional applications. Precisely exploring its thermal conductivity is crucially important to evaluate its thermal transport reliability as high‐temperature structural component and electronic device. In this paper, temperature‐dependent lattice thermal conductivity of Si2 N2 O is studied based on a method integrating density functional theory calculations and experimental measurements. The relationship between the complex crystal structure (or heterogeneous chemical bonding) and lattice thermal conductivity of Si2 N2 O is studied. We herein show that Si2 N2 O intrinsically has moderately high lattice thermal conductivity [30.9 W·(m·K) −1 at 373 K], but extrinsic phonon scattering mechanisms, such as phonon scattering by point defects and grain boundaries etc., might significantly degrade the magnitude in experimental measurement [15.0 W·(m·K) −1 at 373 K]. This work suggests the significance that understanding the intrinsic thermal conductivity, namely the upper limit value, is a precursor to deciphering the more complicated heat transport behavior of Si2 N2 O.